2009
DOI: 10.1158/1078-0432.ccr-08-1229
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Tumor Profiling for Type 1 and Type 2 Papillary Renal Cell Carcinoma

Abstract: Purpose: The goal of this study was to evaluate immunohistochemical and cytogenetic features and their prognostic value in papillary renal cell carcinoma (PRCC) subtypes. Experimental Design: One hundred fifty-eight cases of PRCC were identified and reclassified by subtype. Tumoral expression of 29 molecular markers was determined by immunohistochemistry. Cytogenetic analyses were done on a prospective series of 65 patients. Associations with clinicopathologic information and disease-specific survival were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
2
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 38 publications
12
121
2
8
Order By: Relevance
“…In a study by Klatte et al (15) a cytogenetic analysis was performed to distinguish between the tumor profiles of type I and type II PRCCs. The authors found that loss of chromosome 1p and 3p, and gain of 5q were exclusively observed in type II PRCC, whereas trisomy 17 was more frequent in type I (15). Analysis of the genetic profiles of the PRCC cases in the present study, which comprised six cases of type II and one case of type I, were compatible with this previous report, and the single case of type I PCRR showing trisomy 17 (Table I).…”
Section: Losssupporting
confidence: 91%
“…In a study by Klatte et al (15) a cytogenetic analysis was performed to distinguish between the tumor profiles of type I and type II PRCCs. The authors found that loss of chromosome 1p and 3p, and gain of 5q were exclusively observed in type II PRCC, whereas trisomy 17 was more frequent in type I (15). Analysis of the genetic profiles of the PRCC cases in the present study, which comprised six cases of type II and one case of type I, were compatible with this previous report, and the single case of type I PCRR showing trisomy 17 (Table I).…”
Section: Losssupporting
confidence: 91%
“…Recently, among patients with clear cell RCC, deletions of 3p were associated with a better prognosis (p ϭ .03) than with loss of 4p, 9p, and 14q, which were associated with a significantly poorer prognosis [63]. In papillary type 1 and type 2 tumors, poorer survival was noted with loss of 9p and 3p, whereas trisomy 17 was associated with a more favorable prognosis [64].…”
Section: Prognostication/predicting Response To Therapymentioning
confidence: 99%
“…The papillary cores often contain edema fluid, foamy macrophages, and psammoma bodies. Several clinical reports identified type I tumors as being more frequently multiple, bilateral, indolent, low-grade pRCC, whereas type II were associated with higher grade and poor prognosis tumors related to metastatic spread (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%